(untitled) (Social and Environmental Law Journal, 2023)
Twenty of the twenty-seven units of the federation carry out investigation and fire expertise activities and have been showing positive results in some Fire Departments, such as those in Santa Catarina, Espírito Santo and Distrito Federal. In this way, the objective of this work is to understand how the management of data, collected in the execution of fire expertise carried out by the military firefighters of Goiás, can result in the production of scientific knowledge that can support institutional managers in the processes and decision-making applied implementation of the Fire Safety Operational Cycle in Goiás. Then was made bibliographic about the themes discussed here, associated with field research through the submission of questionnaires to the Fire Departments of all country related to the activity of fire investigation. The content of the fire expert form model used by firefighters in Goiás was also analyzed. It was concluded that the fire expertise service is important in obtaining scientific information about accidents and, based on the results found, actions were proposed to improve this institutional activity, a fact that has the potential to significantly contribute to the improvement of services that the Corporation provides.